2021
DOI: 10.1039/d1sm00176k
|View full text |Cite
|
Sign up to set email alerts
|

A sulfamethoxazole molecularly imprinted two-dimensional photonic crystal hydrogel sensor

Abstract: In this paper, a molecularly imprinted two-dimensional photonic crystal hydrogels sensor (SMZ-MIPCH) for sensitive and label-free recognition of sulfamethoxazole (SMZ) was prepared. Investigating SMZ-MIPCH sensor response performance by measuring the...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…The diffraction images corresponding to different values of P reveal diffraction rings indicative of polycrystalline microstructures without any preferred domain orientation, as reported for other hard sphere and hard sphere-like systems. [47][48][49] As such, there are no distinguishable Bragg peaks. During compression, the position of the diffraction ring remains nearly unchanged (D SALS c-c = 719 AE 15 nm).…”
Section: Application Of Lt-sals To Other Colloidal Systemsmentioning
confidence: 99%
“…The diffraction images corresponding to different values of P reveal diffraction rings indicative of polycrystalline microstructures without any preferred domain orientation, as reported for other hard sphere and hard sphere-like systems. [47][48][49] As such, there are no distinguishable Bragg peaks. During compression, the position of the diffraction ring remains nearly unchanged (D SALS c-c = 719 AE 15 nm).…”
Section: Application Of Lt-sals To Other Colloidal Systemsmentioning
confidence: 99%
“…A 2D molecularly imprinted photonic crystal hydrogels (MIPCH) sensor was made by Cao et al in order to sense sulfamethoxazole (SMZ) [ 114 ]. Their sensor was relatively similar to the previous example except their binding pocket was made specifically for SMZ.…”
Section: Drug Sensingmentioning
confidence: 99%
“…( B ) Dependence of the normalized diffraction spectra of SMZ–MIPCH on the SMZ concentration. (The measurement angle between the probe and the normal range to MIPCH is 21°) (Reprinted with permission from [ 114 ]. Copyright 2021 Royal Chemical Society).…”
Section: Figurementioning
confidence: 99%
“…The result demonstrated that although the reported LOD values of MIP-sensors range from 103 to 105 nM, the lowest values are still comparable with the LOD values reported for the HPLC technique (0.031–0.047 nM) [ 176 ]. Moreover, an even lower LOD value of 107 nM was reported for the molecularly imprinted two-dimensional photonic crystal hydrogel sensor for the label-free recognition of sulfamethoxazole [ 105 ]. Nevertheless, despite these promising results achieved for MIP sensors on the laboratory scale, the large-scale use is still problematic, due to several challenges in the synthesis (see Section 5 ), mass-scale production and commercialisation.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%